A Structural and Influential Analysis of Preschool Shadow Teachers’ Inclusive Education Literacy: Evidence from 73 Respondents - Guo, Pu; Wang, Zeyu (Journal of Ecohumanism, 2025)
This study aims to explore the structural dimensions and influencing factors of inclusive education literacy among preschool shadow teachers. Using survey data and qualitative interviews from 73 shadow teachers in Hohhot, Inner Mongolia, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to confirm the structure of inclusive education literacy, encompassing professional knowledge, professional skills, attitudes toward inclusion, communication and collaboration abilities, availability of support resources, and perceived challenges. The findings revealed a moderate overall level of inclusive education literacy among shadow teachers. Professional training experiences, practical experience, and support resources significantly and positively impacted the level of inclusive education literacy. Notably, perceived challenges were found to have a positive predictive role. The study recommends establishing standardized training and certification systems, enhancing institutional support, clarifying role definitions and collaborative mechanisms for shadow teachers, and focusing on their career sustainability to improve the quality of preschool inclusive education.